Temperature dependent surface morphological modifications of hexagonal WO3 thin films for high performance supercapacitor application. (10th January 2017) - Shinde, Pragati A.; Lokhande, Abhishek C.; Chodankar, Nilesh R.; Patil, Amar M.; Kim, Jin H.; Lokhande, Chandrakant D.
Abstract: In present article, temperature dependent surface morphological modification and its subsequent influence on electrochemical performance of hexagonal WO3 (h-WO3 ) thin films has been investigated. The nanostructured h-WO3 films are synthesized on carbon cloth substrate using simple hydrothermal method. It is observed that h-WO3 thin films prepared at temperature of 413, 433 and 453 K display nanogranule-like, nanoplate-like and nanorod-like suface morphology. The X-ray diffraction study discloses the prominent orientation along (001) and (200) planes which reveals the preferential growth direction of h-WO3 along c and a-axis, respectively. The h-WO3 film prepared at 453 K shows good surface area, pore volume and uniform pore size distribution. The electrochemical measurements exhibit high specific capacitance of 694 F g −1, energy density of 25 Wh Kg −1 and long term cycling performance (87 % capacitance retention after 2, 000 cycles) for h-WO3 thin film. The results indicate that h-WO3 nanorods could be a promising electrode material for high performance energy storage devices.